Analisis Motivasi Siswa dalam Memilih Ekstrakurikuler Basket (Survei Pada SMP Muhammadiyah 10 Surakarta) - Renaldi, Ragil Iqbal; Warthadi, Anugrah Nur; Jariono, Gatot; Nurhidayat, Nurhidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine students' motivation in taking part in extracurricular activities carried out at SMP Muhammadiyah 10 Surakarta, this research also aims to see children's mindset regarding what they get in the field while participating in extracurricular activities and also become a reference for trainers to provide effective learning during activities. Extracurricular. The method used in this research was distributing questionnaires to extracurricular students at SMP Muhammadiyah 10 Surakarta. Student motivation in participating in basketball extracurricular activities at SMP Muhammadiyah 10 Surakarta in the agreed category was 31.25%, and in the strongly agree category was 68.75%. These results, mean that student motivation in participating in basketball extracurricular activities is very high, this is because of support from various parties related to basketball extracurricular activities such as the school, teachers or coaches, and the student's parents themselves. In conclusion, the motivational factors that motivate students will encourage them to take part in basketball extracurricular activities. If this motivation can always be strengthened then students will be enthusiastic about taking part in basketball extracurricular activities. Keywords: Basketball, Extracurricular, Student Motivation